Vermiculite and shading in the formation of ’Rangpur’ lime rootstock - Andreon Viçosi, Karen; Lopes, José Carlos; de Oliveira Garcia, Giovanni; Muniz de Lima, Paula Aparecida; Oliveira Baptista , Julcinara; Sobreira Alexandre , Rodrigo (Comunicata Scientiae, 2022)
‘Rangpur’ lime (Citrus limonia Osbeck cv. Cravo) is widely used as a rootstock for citrus seedlings, although factors such as luminosity and substrate composition are extremely important to obtain quality seedlings. The objective of this study was to analyze the formation of ‘Rangpur’ lime seedlings grown in different substrates and luminosities. A 3x4 factorial arrangement was used in an RBD with four replications of twelve plants. Three luminosities (full sun, 35%, and 70% shading) and four substrate: vermiculite proportions were tested (S1-1: 0, S2-2: 1, S3-1: 2, and S4-0: 1). The seeds were sown in 280 cm3 tubes and emergence was evaluated every two days for 30 days, and biometric assessments at 30, 60, 90, and 120 DAE by measuring the height, diameter, leaves, and mortality. Root length and shoot and root dry mass were measured at 30 and 120 days. Seeds in full sun showed high ESI values and a shorter time period, as well as high mortality at 120 DAE. Highly shaded environments cause etiolation and reduce biomass accumulation and the DQI. Seeds in S4 showed lower results for most variables. It is recommended to use 35% shading associated with the substrate proportions S1, S2, and S3.